STRATEGI KOMUNIKASI PEMERINTAH TERHADAP MASYARAKAT MENGENAI KEBIJAKAN LARANGAN MUDIK LEBARAN TAHUN 2021 PADA PADEMIC COVID 19 - Ria Yunita; Amalliah Amalliah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
Government efforts to prevent the spread of the Covid 19 virus continue to be carried out, such as issuing a policy to prohibit the 2021 Eid homecoming as an effort to avoid a large wave of transmission of the Covid 19 virus. This policy has been informed and has also been disseminated to the public through news in print, social and televi media. and radio. This is done so that the public obeys the regulations issued by the government. Through mass communication theory and Laswell, it is hoped that the message conveyed can be understood by the community, although a small number of people still reject it because returning to their hometown has become a tradition. By observing and collecting data in the field, the community supports this policy but asks the government to provide concessions or alternative choices to the community.